Enhancing mathematical literacy among prospective teachers: Effectiveness of an RME-based learning design - Dahlan, Taufiqulloh; Iskandar, Dadang; Rohimah, Siti Maryam; Nurhadi, Moh.; Hamdani, Acep Roni (Universitas Hamzanwadi, 2025)
Textbooks exert minimal influence on learning outcomes, underscoring the urgent need to develop high-quality, context-responsive teaching materials for prospective educators. This study designed, validated, and evaluated Realistic Mathematics Education (RME)-based instructional materials using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework. Participants included 60 prospective teachers from Pasundan University, randomly assigned to experimental (RME-based materials) and control (conventional textbook) groups. Data were collected through observations, questionnaires, and achievement tests, with ANOVA used for analysis. Expert validation scores were high: material experts (91.86%), learning model experts (92.58%), and peers (92.40%), confirming strong validity. Practicality was similarly high, with small-group and large-group student assessments scoring 92.40% and 92.03%, respectively. Post-intervention, the experimental group outperformed the control group significantly (mean scores: 91.8 vs. 69.5; Δ = 22.3), supported by robust statistical evidence: F(1,47) = 45.07, p < 0.001, η² = 0.49, Cohen’s d = 1.39—indicating a large effect size. Findings confirm the RME-based materials are valid, practical, and highly effective in improving prospective teachers’ learning outcomes. Broader implementation and adaptation to other mathematics topics are strongly recommended.